Impacts of carbohydrate‐restricted diets on micronutrient intakes and status: A systematic review. (22nd April 2019) - Churuangsuk, Chaitong; Griffiths, Daniel; Lean, Michael E.J.; Combet, Emilie
Summary: A systematic review of published evidence on micronutrient intake/status with carbohydrate‐restricted diets (CRD) was conducted in Web of Science, Medline, Embase, Scopus, CENTRAL, andClinicalTrials.gov up to October 2018. We identified 10 studies: seven randomized controlled trials (RCTs) ("Atkins"‐style, n = 5; "Paleolithic" diets, n = 2), two Atkins‐style noncontrolled trials and one cross‐sectional study. Prescribed carbohydrate varied 4% to 34% of energy intake. Only one noncontrolled trial prescribed multivitamin supplements. Dietary intakes/status were reported over 2 to 104 weeks, with weight losses from 2 to 9 kg. No diagnoses of deficiency were reported. Intakes of thiamine, folate, magnesium, calcium, iron, and iodine all decreased significantly (−10% to −70% from baseline) with any CRD types. Atkins diet trials (n = 6; 4%‐34%E carbohydrate) showed inconsistent changes in vitamin A, E, and β‐carotene intakes, while a single "Paleolithic" diet trial (28%E carbohydrate) reported increases in these micronutrients. One other "Paleolithic" diet (30%E carbohydrate) reported a rise in moderate iodine deficiency from 15% to 73% after 6 months. In conclusion, few studies have assessed the impacts of CRD on micronutrients. Studies with different designs point towards reductions in several vitamins and minerals, with potential risk of micronutrient inadequacies. Trial reporting standards are expected to include analysis of micronutrient intake/status. Micronutrients in foods and/or supplements should be considered when designing, prescribing or following CRDs.